Molecular pathogenesis of diffuse large B-cell lymphoma (Hematology Meeting Reports, 2009)
Diffuse Large B-Cell Lymphomas (DLBCLs) are the most common histologic subtype within non-Hodgkin’s lymphomas (NHLs), accounting for approximately 30% of them. These lymphomas are a heterogeneous clinicopathologic entity characterized by marked phenotypic and clinical differences and several data indeed suggest that under the name of DLBCL different disease entities are currently included. This vision is supported by the fact that DLBCL subtypes are characterized by different cells of origin and by different cytogenetic and molecular aberrations and, therefore, by a distinct pathogenesis.